Dampak Implementasi International Financial Reporting Standard Pada Penyajian Other Comprehensive Income Perusahaan Perdagangan, Jasa, dan Investasi di Indonesia - Denny Rianto; Nurmala Ahmar (Magister Akuntansi Universitas Pancasila, 2018)
ABSTRACT The purpose of this study is to analyze the presentation of other comprehensive income and its components in the trade, service and investment industries after the implementation of the International Financial Reporting Standard in Indonesia. The sample is the trade, service and investment industry sectors listed in Indonesia Stock Exchange 2012-2015. Other Comprehensive Income (OCI) shall be presented separately in the statements of income since 2013 and re-review for 2012 on the reporting of the relevant year. The components presented include asset revaluation, translation of foreign currency financial statements to reporting currency, actuarial changes in defined benefit obligations, changes in fair value in available-for-sale investments, fair value changes to current, joint and joint venture hedges. The result of the research shows that there is difference of presentation value of other comprehensive comprehensive component. Future research can examine the antecedents and consequent accounts of OCI components in public companies in Indonesia. ABSTRAK Tujuan penelitian ini adalah menganalisis penyajian other comprehensive income dan komponennya pada industri perdagangan, jasa, dan investasi pasca penerapan International Financial Reporting Standard di Indonesia. Sampel adalah sektor industri perdagangan, jasa, dan investasi yang terdaftar di Bursa Efek Indonesia tahun 2012-2015. Other Comprehensive Income (OCI) wajib disajikan secara terpisah pada laporan laba rugi sejak tahun 2013 dan saji ulang untuk tahun 2012 pada pelaporan tahun yang besangkutan. Komponen yang disajikan mencakup revaluasi aset, penjabaran laporan keuangan mata uang asing ke mata uang pelaporan, perubahan aktuarial dalam imbalan kerja manfaat pasti, perubahan nilai wajar dalam investasi yang tersedia untuk dijual, perubahan nilai wajar terhadap lindung nilai arus, asosiasi dan ventura bersama. Hasil penelitian menunjukkan terdapat perbedaan nilai penyajian komponen other comprehensive income. Riset mendatang dapat meneliti anteseden dan konsekuen akun komponen OCI pada perusahaan public di Indonesia. JEL Classification: M41, M48